Effect of art therapy and play therapy on anxiety among hospitalized preschool children - Dalei, Sweta Rani; Nayak, Geeta Rani; Pradhan, Rubi (Journal of Biomedical Sciences, 2020)
Background: Play is a tremendous method of communication, expansion of social relationship and communal understanding. Admission into the hospital leads to anxiety and strain for children due to alteration in the settings and their health conditions. Children suffer from separation anxiety; they are not cooperative and do not allow nurses to do any invasive procedures. So the study aimed to find out the anxiety level and role of art and play therapy to overcome it. Material and methods: Sixty preschool hospitalised children were selected for the study. Data were collected through a self-structured questionnaire on socio-demographic and hospitalisation anxiety scale. Descriptive and inferential statistics were used to analyse the data. Results: The study findings revealed that 75%, 20% and 5% of children had moderate, severe and mild anxiety during hospitalisation. There was a significant difference observed between pre-test and a post-test mean score of anxiety level in art and play therapy at p<0.0001. A significant relationship was observed between the duration of hospitalisation and anxiety level. Conclusion: The present study's findings conclude that art therapy and play therapy are cost-effective, convenient, and require less skill to reduce anxiety among hospitalised preschool children.